Reputation Risk and Its Impact on the Islamic Banks: Case of the Murabaha - Haron, Mohamad Sabri; Ramli, Rashila; Injas, Malek Marwan Yousef; Injas, Raghad Azzam (International Journal of Economics and Financial Issues, 2015)
Murabaha to the purchase orderer is a rival product in the Islamic banking system. It is implemented in the most of Islamic banks (IBs). However, there is a controversy among contemporary jurists (SSBs) in the mechanism of the implementation of this product. The objective of this study is to show the controversial issues related to the product of Murabaha and to identify its impact on the bank’s reputation. This study is an exploratory study therefore, based on the literature review relating to the issues of Murabaha to the purchase orderer (MPO), reputation risk, and non-compliance risk. This study tries to describe and reveal the relationship between reputation and non-compliance risk. As well as revealing the impact of reputation risk on the IB stability and financial performance. It aims to brought the attention of decision-makers regarding consequences of these risks. At the end of this paper, concluded that the IBs like all other corporations, affected by the risks reputation, despite their principles that based on Islamic precepts. Keywords: Murabaha to the purchase orderer; reputational risks; non-compliance risks; Islamic bank JEL Classifications: G21; G32; G33